Genetic Potential and Inheritance Pattern of Phenological Growth and Drought Tolerance in Cotton (Gossypium Hirsutum L.) - Mahmood, Tahir; Wang, Xiukang; Ahmar, Sunny; Abdullah, Muhammad; Iqbal, Muhammad Shahid; Rana, Rashid Mehmood; Yasir, Muhammad; Khalid, Shiguftah; Javed, Talha; Mora-Poblete, Freddy; Chen, Jen-Tsung; Shah, Muhammad Kausar Nawaz; et al. (Frontiers in Plant Science, 2021)
Cotton (Gossypium hirsutum L.) has prime importance in the global economy and governs the socio-economic affairs of the world. Water scarcity and high temperature are major constraints that badly affect cotton production, which shows the need for the development of drought-tolerant varieties. Ten cotton genotypes, including 3 drought-tolerant and 7 susceptible, were identified from a panel of diverse cotton genotypes at the seedling stage under two contrasting water regimes. Three lines were crossed with seven testers under line x tester mating design. The 21 F1 cross combinations along with 10 parents, were evaluated under 100% filed capacity (non-stressed, NS) and 50% filed capacity (drought-stressed, DS) to assess the effects of drought stress and its inheritance in the next generation. All the genotypes were evaluated till the maturity stage for combining ability, heritability and other genetic factors to understand the drought tolerance mechanisms. The obtained results revealed that most of the studied traits, including days taken to maturity, yield traits, and physiological traits, are under significant genetic control, with a strong genetic basis and have a huge potential for improving drought tolerance of cotton. Drought tolerance was found to have a strong association with early maturity and agro-climatic conditions of the cultivated areas. Considering the inheritance behavior of drought tolerance and the differential response of cotton genotype toward drought stress, here we have proposed new breeding objectives and strategies to cop the drought stress damages in cotton. Identified superior parents in this study are suggested to use in the future breeding program to advance the individual traits under water-limited conditions.